Port au Port : from British surveys between 1893 and 1895 - United States. Hydrographic Office (Washington, D.C.)
Black and white. Three compass roses with 360 degree rings. Relief shown by form lines and spot heights. Depths shown by soundings. Includes conversion table for depths. -- On bottom edge: "4th ed., Nov. 1918" and "Small corrections [.] May '43."